Occupant presence and behavior: A major issue for building energy performance simulation and assessment. (December 2020) - Laaroussi, Y.; Bahrar, M.; El Mankibi, M.; Draoui, A.; Si-Larbi, A.
Highlights: Occupant behavior is a main factor influencing the building energy performance. Synthetic review about the occupant presence and occupants' interactions was presented. Monitoring approach, occupant modeling and energy feedback programs are the key approaches for human behavior analysis. The integration of social science is essential for the analysis process of the occupant behavior topic. Abstract: The building sector in the world is responsible for nearly 36% of the final energy consumption and nearly 40% of total direct and indirect CO2 emissions. Reducing buildings energy consumption is an absolute necessity, and one of the most efficient methods is the estimation and optimization of building energy performance. One of the significant factors affecting the building energy performance is the occupant behavior. Recently, there has been growing interest in the occupant behavior field. Within the framework of this context, different methods have been proposed and developed especially when the traditional methods, such as interview and survey, are not efficient and sufficient to analyze and to predict the occupant behavior with better accuracy. This research provides a comprehensive characterization of the occupant behavior through, a review of current approaches for occupant behavior analysis. The main key issues and drivers affecting the energy behavior of habitants identified on the literature were synthetized and presented. Furthermore, the paper highlights the necessity of including the energy feedback programs as a main key in the topic of occupants, in order to integrate them in the building performance process. This research is a part of a European project H2020 "Holistic Energy and Architectural Retrofit Toolkit (HEART)".